2021
DOI: 10.24815/jipi.v5i2.20713
|View full text |Cite
|
Sign up to set email alerts
|

Online Professional Development for Improving Teacher's STEM PCK Competence, Can It Be An Alternative? (An Evaluation Using the CIPP Model)

Abstract: During the pandemic, face-to-face training should not be carried out to reduce the spread of the covid outbreak. Therefore, online teacher professional development is an alternative method to replace the face-to-face training. In a program implementation, evaluation is an important component to determine whether the program has been implemented well or not. This evaluation is important to determine the effect of this online training on improving STEM PCK teachers. The evaluation used the CIPP model (Context, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…Alimohammadi et al (2013) to check the effectiveness of a health program using by CIPP model also supported the results of this study because they observed that the respondents were of the view that improvement in the process of the program was required. The study, however, shows a divergence from the reports of Hasanah et al (2021),, which demonstrated that the respondents were 100% satisfied with the implementation process of an online professional development program. Darma (2019) debated that the process (implementation), which includes teaching methods, medium of instruction, materials related to teaching, and assessment has an important role in reshaping the educational system and quality of an education program.…”
Section: Discussioncontrasting
confidence: 70%
“…Alimohammadi et al (2013) to check the effectiveness of a health program using by CIPP model also supported the results of this study because they observed that the respondents were of the view that improvement in the process of the program was required. The study, however, shows a divergence from the reports of Hasanah et al (2021),, which demonstrated that the respondents were 100% satisfied with the implementation process of an online professional development program. Darma (2019) debated that the process (implementation), which includes teaching methods, medium of instruction, materials related to teaching, and assessment has an important role in reshaping the educational system and quality of an education program.…”
Section: Discussioncontrasting
confidence: 70%
“…Pre-service primary school teachers' views on their competencies to implement STEM education were examined, and it was determined that they mostly saw themselves as inadequate. Hasanah et al (2021), determined that online professional development is very useful for teachers and can develop their skills in implementing STEM learning during distance learning. Apart from low-cost, online PD can be an alternative way to improve teachers' STEM PCK competence.…”
Section: Results Related To Pre-service Primary School Teachers' View...mentioning
confidence: 99%
“…Faikhamta, Lertdechapat, & Prasoblarb (2020) examined the effects of a PCK-based STEM professional development program on science teachers and concluded that it positively affected science teachers' attitudes toward STEM education. In addition, some studies have been conducted on teachers' STEM PCK competence (Hasanah, Permanasari, & Riandi, 2021) and Supporting PCK and CK Development of pre-service primary school teachers through a STEM program (Correia & Baptista, 2022). Since there are few studies in the literature, further research on STEM and PCK needs to be developed (Hasanah, Riandi, Kaniawati, & Permanasari, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers design learning by utilizing technology (technology knowledge). Hasanah et al, (2021) revealed that online TPD could be a good alternative to implementing teacher training programs. Involving technology in the TPD program can increase teachers' technology knowledge over time and pedagogical beliefs about scientific inquiry, and teachers show high interest in the TPD program (Lee et al, 2017).…”
Section: Resultsmentioning
confidence: 99%